A review on the thermal performance of nanofluid inside circular tube with twisted tape inserts. (June 2020) - Ahmad, Saadah; Abdullah, Shahrir; Sopian, Kamaruzzaman
Working fluid with higher thermal conductivity and tube with better fluid mixing are two crucial elements for heat transfer enhancement in heat exchanger system. Hence, several methods and techniques have been explored to improve heat transfer efficiency, including dispersing nanoparticles into conventional heat transfer fluid and inserting instruments inside the tube of the heat exchanger. Studies have shown that nanofluid can improve heat transfer efficiency of the system due to its higher thermal conductivity and drastic Brownian motion of nanoparticles while inserts within tube can improve heat transfer efficiency by increasing axial velocity of working fluid for better fluid mixing. This article summarized 109 of journals from recent research on heat transfer enhancement of nanofluid flowing inside the tube with inserts as well as discussing the significant parameters that affected the system's efficiency such as nanoparticles' volume fraction, Reynolds number and types and configurations of inserts. Ultimately, analysis will be carried out to determine the most suitable modification of twisted tape inserts with the most optimum value of nanoparticle volume fraction for turbulence flow regime. Finally, some problems that need to be solved for future research such as agglomeration and pressure drop are discussed.